An Investigation of the Relationship between Workaholism and Organizational Commitment of Primary School Teachers - Murat Özdemir; Yasemin Kalaycı Türk; Sabahattin Sümer; Ahmet Aypay (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2021)
Purpose: The individuals' workaholic tendencies are assumed to be reflected in their attitudes and behaviours in the workplace. Thus, the present study aimed to reveal the relationship between the workaholic tendencies of primary school teachers and their organizational commitment. Design/Methodology/Approach: A correlational survey model, among the quantitative research methodologies, was adopted in the study. The research sample consisted of 301 primary school teachers working in public primary schools in a metropolitan municipality city center in southeast Turkey. The research data were collected through the Organizational Commitment Scale and the Workaholism Battery. Findings: Affective commitment scores of the participating teachers are partially high while the normative commitment and continuance commitment scores are neutral. Regarding workaholism tendencies, e teachers have a high level of perception for enjoyment and work involvement through their drive perceptions are moderately high. Male teachers and those between 20-25 have higher workaholic tendencies of 38.9% grand total. The sub-dimensions of enjoyment and drive significantly predict affective and normative commitment while the work involvement sub-dimension of workaholism predicts continuance commitment. Implications/Originality/Value: The effects of workaholism should be considered for future practices and research aimed at teacher commitment to be carried out in educational settings.